2016
DOI: 10.1089/can.2015.0001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cannabinoid Receptors in Human Osteoarthritic Cartilage: Implications for Future Therapies

Abstract: Introduction: Cannabinoids have shown to reduce joint damage in animal models of arthritis and reduce matrix metalloproteinase expression in primary human osteoarthritic (OA) chondrocytes. The actions of cannabinoids are mediated by a number of receptors, including cannabinoid receptors 1 and 2 (CB1 and CB2), G-protein-coupled receptors 55 and 18 (GPR55 and GPR18), transient receptor potential vanilloid-1 (TRPV1), and peroxisome proliferator-activated receptors alpha and gamma (PPARα and PPARγ). However, to da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 64 publications
(81 reference statements)
1
47
0
Order By: Relevance
“…It is demonstrated from both sides that CIH caused by OSAS could cause ECS disorder and finally result in bone metabolic disorder and abnormal bone structure. Studies [24] have shown that both CB1 and CB2 receptors are expressed on mouse osteoblasts and bone marrow mesenchymal stem cells. Studies [25] have also proved that decrease in expression of CB1 receptor could relieve bone metabolic abnormality caused by ECS disorder, which is the same as the result of this test.…”
Section: Discussionmentioning
confidence: 99%
“…It is demonstrated from both sides that CIH caused by OSAS could cause ECS disorder and finally result in bone metabolic disorder and abnormal bone structure. Studies [24] have shown that both CB1 and CB2 receptors are expressed on mouse osteoblasts and bone marrow mesenchymal stem cells. Studies [25] have also proved that decrease in expression of CB1 receptor could relieve bone metabolic abnormality caused by ECS disorder, which is the same as the result of this test.…”
Section: Discussionmentioning
confidence: 99%
“…The non‐psychoactive cannabinoid, cannabidiol (CBD), can be an effective oral anti‐arthritic therapy (Malfait et al ., ). Moreover, CBD can reduce bone resorption, possibly by modulating GPR55 receptor signalling (Dunn et al ., ). However, GPR55's actions are still unclear, and further research is essential to foster a deeper understanding of its role in bone metabolism, especially under pathophysiological conditions.…”
Section: Subchondral Bone In the Pathogenesis Of Oa: Role Of Cannabinmentioning
confidence: 97%
“…Nevertheless, it was also shown to work in synergy with TNFα to cleave caspase‐3 and induce apoptosis, thus facilitating cartilage degeneration (Gómez et al ., ). Therefore, it is important to further identify the role of these receptors within normal and OA cartilage to clarify their role in healthy tissue and their potential as possible targets in the treatment of OA (Dunn et al ., ).…”
Section: Effects Of Cannabinoids On Osteoarthritic Cartilagementioning
confidence: 99%
“…These receptors are considered not to be directly targeted by CBD, but other studies have confirmed indirect CBD‐mediated agonism and antagonism of the CB1 receptor . Both the CB1 and CB2 receptor are expressed in human articular cartilage as well as the C28/I2 cell line, and we, therefore, investigated whether the CBD‐induced Ca 2+ influx is influenced by blockage of those receptors. We were able to demonstrate a decrease of the CBD‐evoked Ca 2+ amplitude in Fura‐2 assays by specifically blocking the CB1 receptor, whereas blocking the CB2 receptor left the signal unaffected.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical studies have demonstrated that CB1 and CB2 receptor messenger RNA and proteins are expressed in the synovia of OA and rheumatoid arthritis patients and that the ECs 2‐AG and AEA were present in the synovial fluid of these patients, but not in the synovia of individuals without joint symptoms . Cannabinoid receptors are expressed in human OA cartilage, human primary chondrocytes and in osteocytes of the underlying bone …”
mentioning
confidence: 99%